ABC University Rebranding Strategy in Order to Build A New Image to Attract The Interest of Prospective Students - Fitriyanti, Neng Putri; Ali, Mochammad Mukti (Dinasti Publisher, 2025)
This study examines the rebranding strategy implemented by ABC University as part of a strategic transformation to enhance competitiveness and attract prospective students. Using SWOT analysis and the STP (Segmenting, Targeting, Positioning) approach, the research identifies the university’s strengths in its continuously updated curriculum, industry partnerships, and integrated learning technology. However, challenges arise from pricing competition, inconsistent social media image, and suboptimal market segmentation. The findings indicate that a focused STP strategy can strengthen the university’s image and increase its appeal in the higher education market. By leveraging technological trends and international partnerships, Universitas ABC is expected to build a more relevant and competitive new identity.